Peran self efficacy dalam memoderasi pengaruh digital literacy terhadap entrepreneurial intention - Dominikus Rojoki Manullang; Ikaputera Waspada (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2022)
This research is motivated by the low entrepreneurial intention of Vocational High School (VHG) students in East Jakarta. This study aims to determine and analyze the mediating effects of self-efficacy on the effect of digital literacy on students' entrepreneurial intention. The method used in this study is an explanatory survey research with data collection techniques through questionnaires and observations. The population of this study were all students SMK 22 dan 67 in Jakarta Timur of class XI class 2021/2022 as many as 316 students, while based on Slovin calculations the sample of this study was 70 students. The collected data were then analyzed using descriptive analysis techniques and multiple linear regression with Moderate Regression Analysis (MRA). The results showed that: 1) the level of digital literacy, self-efficacy, and entrepreneurial of students were in the very high category. 2) Digital literacy affects the entrepreneurial intention of students. 3) self-efficacy mediate the effect of digital literacy on students' entrepreneurial intention. These findings indicate that to increase intention in entrepreneurship, the learning process in SMK needs to be emphasized on efforts to increase digital literacy and self-efficacy